Portfolio optimization for risk averse and risk seeking investor - Heckenbergerová, Jana; Šild, Petr (Slovenská technická univezita v Bratislave, 2018)
The goal of this work is to optimize portfolio for two types of investors: risk averse and risk seeking investor. The main purpose of optimization is to make the highest profit as possible in investing into the mutual funds with bearable risk corresponding to investor's profile. As input to this work is selection from equity, bond and commodity funds offered by ČSOB Asset management, because of the largest offer on the Czech market.
Optimalizace portfolia pro dynamického a opatrného investora
Keywords: Portfolio optimization; Profitability; Simplex method; Volatility; Yield